Recent Advances in the Use of Black TiO2 for Production of Hydrogen and Other Solar Fuels. Issue 10 (4th February 2019) - Chatzitakis, Athanasios; Sartori, Sabrina
Abstract: Black TiO2 has emerged as one of the most promising photocatalysts recently discovered. The reason behind its catalytic activity is considered to be due to the presence of defects and Ti 3+ species at the surface of black TiO2 nanostructures, which are crucial for its diverse applications. Moreover, disordered/crystalline surface layers and bulk regions have been identified and appear to influence the intrinsic properties of the material. Here, we present the latest studies on the use of black TiO2 for metal free hydrogen production, as well as for CO2 photoreduction and N2 photofixation. After highlighting the structure/property relations, we conclude with some critical questions and suggest further topics of research in order to better understand the underlying mechanisms of light absorption in black TiO2, especially towards solar fuels production. Abstract : TiO2 is a material that never ceases to amaze and the recent discovery of black TiO2 brought it in the forefront of materials research. Black TiO2 is one of the most promising photocatalytic materials with the absorption edge reaching the IR region. This short review provides a glimpse at the most important cutting‐edge research and progress in black TiO2 for hydrogen production from water electrolysis, as well as other important solar fuels such as NH3 and hydrocarbons.